indonesia Penurunan Total Dissolved Solid Untuk Air Minum Dalam Kemasan (Air Demineral) Menggunakan Metode Ion Exchange - Muhtarom, ahmad amiruddin; nofa, alif ya; kustomo, kustomo (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2023)
Water is the most important substance in human life after air. Nearly three fourths of our body is water and no one can survive more than 4-5 days without drinking water. The sources of raw water for drinking water that are most widely used are well water, rivers and Regional Drinking Water Companies. There are at least 3 factors that cause acid mine drainage to form, namely material containing sulfide minerals, water, and air so that the surrounding water supply environment such as rivers, ponds, etc. is also polluted. . In this case practical and hygienic drinking water is an important requirement for people with lifestyles and high mobility in meeting their daily drinking water consumption needs. A treatment machine is provided in the form of 3x2 tubes connected in parallel with a water pipe, the 3 tubes contain cation resin, anion resin and activated carbon. Tirta Mekar Jaya, which owns the trademark AXOGY. Referring to the TDS reduction process, it has been regulated by Permenperind No.